Effects of high-intensity circuit training, low-intensity circuit training and endurance training on blood pressure and lipoproteins in middle-aged overweight men - Paoli, Antonio (BioMed Central, 2013)
BACKGROUND: The aim of this study was to determine the physiological effects of an high-intensity circuit training (HICT) on several cardiovascular disease risk factors in healthy, overweight middle-aged subjects, and to compare the effects of HICT to traditional endurance training (ET) and low-intensity circuit training (LICT). METHODS: Fifty-eight participants (ages 61±3.3 yrs, BMI 29.8±0.9) were randomly assigned to one of the three exercise treatment groups: HICT, LICT and ET. The three groups exercised three times per week, 50 min per session for 12 weeks. Baseline and after intervention anthropometric characteristics: body weight (BW), fat mass (FM); blood pressure: diastolic (DBP) and systolic (SBP), blood parameters; CHOL-t (total cholesterol), LDL-C (low density lipoprotein-cholesterol), HDL-C (high density lipoprotein-cholesterol), TG (triglycerides), ApoB and ratio ApoB/ApoA1 were measured. RESULTS: Compared to other groups, HICT showed significantly higher reductions in FM, DBP, CHOLt, LDL-C, TG, ApoB and significantly greater increases in high density HDL-C. LICT resulted in the greatest reduction in SBP. All groups showed a significant improvement of BW without any significant differences between groups. CONCLUSIONS: Our findings indicate that high-intensity circuit training is more effective in improving blood pressure, lipoproteins and triglycerides than endurance training alone or lower intensity circuit training.